Socio-Economic Status of Parents And Peers Impact on Consumption Behavior of FKIP USK Economic Education Students - Anggraini, Irma; Nuriah, Nuriah; Mustofa, Achmad; Razak, A.; Musfiana, Musfiana (Economic Education and Entrepreneurship Journal, 2023)
This research aims to determine the influence of the socio-economic status of parents and peers on the consumption behaviour of USK FKIP Economics Education students. This research uses a quantitative approach with descriptive research type. The population in this study were active economics education student’s class of 2018. The sample in this study was 51 students. Data collection techniques in this research are literature study and questionnaires. The data analysis technique uses multiple linear regression analysis, and determination test. The results of the determination test prove that there is an influence of 31.8%, the remaining percentage is influenced by other variables not explained in this research. The research results show that the variable of parents' socio-economic status has a negative and insignificant effect on students' consumption behavior. The peer variable has a positive and significant effect on student consumption behavior. Simultaneously, the socio-economic status of parents and peers has a positive and significant effect on consumption behavior. The research results imply that high student consumption causes a person to become consumptive, meaning wasteful and excessive consumption behavior, where there is no priority scale or can also be interpreted as a luxurious lifestyle, so the results of this research can be a person's view on consumption.Keywords: Consumption Behavior, Peers, Socioeconomic StatusDOI: http://dx.doi.org/10.23960/E3J/v6i2.191-197